Formate complexes of tri- and tetravalent titanium supported by a tris(phenolato)amine ligand. Issue 37 (7th September 2022) - Okumura, Akira; Ghana, Priyabrata; Fink, Fabian; Schmidt, Regina; Hoffmann, Alexander; Spaniol, Thomas P.; Herres-Pawlis, Sonja; Okuda, Jun
Abstract : Titanium(iii ) and titanium(iv ) formate complexes supported by the sterically encumbering tris(phenolato)amine ligand (H3 (O3 N) = tris(4, 6-di- tert -butyl-2-hydroxybenzyl)amine) are described. Abstract : Titanium(iii ) and titanium(iv ) formate complexes supported by the sterically encumbering tris(phenolato)amine ligand (H3 (O3 N) = tris(4, 6-di- tert -butyl-2-hydroxybenzyl)amine) are described. Salt metathesis of the chlorido precursor [(O3 N)TiCl] (1-Cl ) with sodium formate in a 2 : 1 ratio in THF gave a dimer of sodium dititanium triformate units with 12-membered ring [Na{(O3 N)Ti}2 (μ-OCHO-η O :η O ′)3 ]2 (3-Na ) when crystallized from acetonitrile. Complex 3-Na was also prepared by reacting the previously reported terminal formate complex [(O3 N)Ti(OCHO)] (2 ) with excess sodium formate. Salt metathesis of 1-Cl with potassium formate gave a tetratitanium cluster of the composition [K3 {(O3 N)Ti}4 (OCHO)7 ] (3-K ) which can be also obtained by treating 2 with potassium formate. In 3-K both Ti and K centers are six-coordinate. The titanium(iii ) complexes [(O3 N)Ti(L)] (4-L, L = THF, THP, Et2 O) and solvent free dimeric [(O3 N)Ti]2 (5 ) were synthesized by reduction of 1-Cl with sodium sand or magnesium in THF, THP, Et2 O, and n -pentane, respectively. The tert -butyl formate adduct of titanium(iii )-[(O3 N)Ti( t BuOCHO)] (6 ) was isolated by reacting 4-L or 5 with tert -butyl formate. Complex 6 is thermolabile and slowly decomposed in solution to produce a formate-bridged mixed-valence titanium(iii )/titanium(iv ) complex [{(O3 N)Ti}2 (μ-OCHO-η O :η O ′)] (7 ) which further decomposed to a mixture containing 2, [(O3 N)Ti(OH)] and [(O3 N)Ti–O–Ti(O3 N)]. All new complexes were isolated in moderate to good yields and fully characterized by elemental analysis, 1 H and 13 C NMR spectroscopy, and single crystal X-ray diffraction analysis. For the titanium(iii ) complexes solution magnetic moments were measured by the Evans method and EPR spectra recorded as toluene glass at 77 K.